1988
DOI: 10.3354/meps048217
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of zooplankton by suspension-feeding bivalves and fish in estuarine enclosures

Abstract: Enclosure experiments were conducted during April. June/July and September in the eutrophc estuary Roskilde Fjord, Denmark, to reveal the effects of inorganic nutrients, suspensionfeedng bivalves Mytilus edulis and planktivorous fish (three-spined sticklebacks Gasterosteus aculeatus) on the zooplankton community > 45 pm. The additlon of inorganic nutrients did not increase zooplankton biomass although it did increase the chlorophyll level, indicating that zooplankton production was not food hmited. Filtration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…This study confirmed the removal of heterotrophic organisms by juvenile mussels (e.g. Horsted et al 1988, Kreeger & Newell 1996. Assuming that heterotrophs, like phytoplankton, also serve as a food source for mussels (e.g.…”
Section: Recovery Responsesupporting
confidence: 66%
See 3 more Smart Citations
“…This study confirmed the removal of heterotrophic organisms by juvenile mussels (e.g. Horsted et al 1988, Kreeger & Newell 1996. Assuming that heterotrophs, like phytoplankton, also serve as a food source for mussels (e.g.…”
Section: Recovery Responsesupporting
confidence: 66%
“…Within the plankton community, 4 groups were distinguished; bacteria, picophytoplankton (defined here as 0.2 to < 3 µm), nanophytoplankton (3−20 µm), and ciliates (20−200 µm). Larger zooplankton were not included in the current study, as we assumed that juvenile mussels do not effectively filter out larger heterotrophs (Horsted et al 1988). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although phytoplankton was traditionally considered the main food source (Nielsen and Maar 2007), several studies have stated the importance of other food particles like dead organic material (Dame and Dankers 1988) and bacteria attached to this (Newell et al 1989), microzooplankton (Horsted et al 1988;Kreeger and Newell 1996;Trottet et al 2008) and, for larger mussels ([22 mm;Horsted et al 1988), mesozooplankton (Davenport et al 2000;Wong and Levinton 2006;Lehane and Davenport 2006).…”
Section: Introductionmentioning
confidence: 99%